Crash Course in Collection Development - Disher, Wayne (Santa Barbara Libraries Unlimited, 2014)
"This indispensable resource provides tools for collection management in public libraries, featuring essential strategies for inventory assessment, market analysis, budgeting, marketing, and customer service. This book is a must-have for those just entering the field or professionals in need of a refresher in effective library operations"--
Library collections -- The library and its community -- Collection assessment and evaluation -- Collection development policies -- Statistics for collection developers -- Managing collection budgets -- Selecting library materials -- Reviews and reviewing sources -- Acquisitions -- The publishing industry -- Collection maintenance -- Mending and preserving -- Collection promotion and merchandising -- Handling complaints about the collection -- Collections for the digital age.
Includes bibliographical references and index.
Keywords: Collection development (Libraries) -- United States; Small libraries -- Collection development -- United States; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / Collection Development; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / General